Abundance and Diversity of Phytoplankton and Zooplankton in Waters of Youtefa Bay Tourism Area - Annita Sari; Ambo Tuwo; Chair Rani; Amran Saru; Yudi Prayitno (Jurnal Segara, 2022)
The waters in Youtefa Bay have degradation due to the transition from mangrove areas to industrial sites, housing, bridge construction and household waste disposal. Water degradation has indirectly affected the growth of plankton. Plankton consists of phytoplankton which is the primary producer of the food chain so that it is utilized by zooplankton as the first consumer. The aim of this study was to determine the abundance and diversity of phytoplankton and zooplankton. This research was conducted during June-August 2019, the method used purposive sampling. Samples were obtained from 6 observation stations. The results showed there is 28 species of phytoplankton (∑160,000 ind/L) and 15 species of Zooplankton (∑ 84,200 ind/L). The diversity index of Phytoplankton is ranging from 1-2.21; Dominance (D) 0.17-0.4 and similarity (E) 0.59-1, while for zooplankton diversity (H’) ranges from 0.97-1.39; Domination (D) 0.07-0.42 and similarity (E) 0.59-1. The Diversity Index shows that the waters of Youtefa Bay have moderate diversity. The similarity between genera is relatively same. The Dominance index value during the observation was seen <0.5 or close to 0, this means that in the community that there was no genus that was extremely dominating the other genera.